Using Mind Mapping to Improve Students’ Reading Comprehension - Nur Zam Zamia; Konder Manurung; Andi Patmasari; Darmawan Darmawan (Hasanuddin University, 2025)
Reading comprehension plays a pivotal role in students’ academic achievement. However, many learners struggle due to traditional teaching methods and limited strategies. To address this challenge, this research investigates whether the use of mind mapping can improve reading comprehension among eighth-grade students at SMP PT Pasangkayu. This research used a quasi-experimental design. The population consists of eighth-grade students from SMP PT Pasangkayu, totaling 85 students from 3 classes. The sample is class B as the experimental class and class C as the control class. Tests were used to collect data consisting of pre-tests and post-tests. The test results show that the average pre-test score obtained by the experimental class is 35.14, while the average pre-test score obtained by the control class is 43.72. Then the average post-test score of the experimental class was 79.64, while the control class was 53.93. The calculated t-value (3.37) was greater than the t-table value (1.674), which means the hypothesis is accepted. The t-test is used to test the significance and relevance between two unpaired sample groups. Based on the research results, the use of mind mapping can improve the reading comprehension of eighth-grade students at SMP PT Pasangkayu.